2016
DOI: 10.1016/j.ijid.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Rubella immunity among pregnant women aged 15–44 years, Namibia, 2010

Abstract: In the absence of a routine rubella immunization program, the high level of rubella seropositivity suggests rubella virus transmission in Namibia, yet 15% of pregnant Namibian women remain susceptible to rubella. The introduction of rubella vaccine will help reduce the risk of rubella in pregnant women and CRS in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
6
10
0
Order By: Relevance
“…No statistically significant difference in rubella IgM and IgG positivity was found in relation to most socio-demographic characteristics of the pregnant women in this study. A similar finding was also reported in a recent study in Southern Ethiopia (Tamirat et al, 2017), and in other studies in Nigeria (Pennap and Egwa, 2016) and Namibia (Jonas et al, 2016). However, a statistically significant association between IgM positivity and area of residence was found in the present study; pregnant women from urban settings had two times the IgM positivity of those from rural settings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No statistically significant difference in rubella IgM and IgG positivity was found in relation to most socio-demographic characteristics of the pregnant women in this study. A similar finding was also reported in a recent study in Southern Ethiopia (Tamirat et al, 2017), and in other studies in Nigeria (Pennap and Egwa, 2016) and Namibia (Jonas et al, 2016). However, a statistically significant association between IgM positivity and area of residence was found in the present study; pregnant women from urban settings had two times the IgM positivity of those from rural settings.…”
Section: Discussionsupporting
confidence: 93%
“…The overall seroprevalence of rubella among pregnant women was found to be 89% (95% CI 86.3-91.3%). A similar finding has been reported from other African countries such as Senegal (90.1%) (Dromigny et al, 2003) and Namibia (85.0%) (Jonas et al, 2016). However, the overall seroprevalence in this study is higher than reports from other African countries like the Democratic Republic of Congo (58.97%) (Zanga et al, 2017), Sudan (65%) (Hamdan et al, 2011), and Nigeria (68%) (Bamgboye et al, 2004), and lower than reports from Burkina Faso (95%) (Tahita et al, 2013a,b) and Zimbabwe (92%) (Mamvura et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, studies conducted in Burkinafaso, Senegal and Iran showed higher rubella seroprevalence (95.0, 90.1 and 96.2%, respectively) among pregnant women [22, 23]. Another study conducted among urban and rural pregnant women in Namibia showed an overall rubella seroprevalence of 85%, with urban women having higher risk of infection [24]. These differences in seroprevalence rates can be attributed to the degree of contamination at national level, the testing method used and/or the size of the sample used.…”
Section: Discussionmentioning
confidence: 99%
“…The main aims of vaccination programs are to prevent rubella infection during pregnancy and to protect CRS. The seroprevalence of rubella virus infection among pregnant women in several countries has been reported [ 16 21 ]. However, the rubella seroprevalence in Chinese pregnant women population has been scantily studied, only one report among Chinese women of reproductive age during preconception period were available to estimate the immune protection level and CRS risk in our country [ 22 ].…”
Section: Introductionmentioning
confidence: 99%